Yoga-based Interventions for Hypertension: A Preferred Reporting Items for Systematic Reviews and Meta-analyses Extension for Scoping Reviews Guided Scoping Review of Clinical Evidence - Prasad, Bawadkar; Kumari, Suketha; Sushma, Durge; S, Dhanu (International Research Journal of Ayurveda & Yoga, 2025)
Background: Hypertension is now a global public health issue and a primary contributor to morbidity and mortality. As complementary non-pharmacological interventions such as yoga are increasingly used to help control blood pressure, evidence is sparse and scattered. Objectives: The objective is to identify systematically, map existing clinical research on yoga-based interventions for hypertension, and identify evidence gaps through a scoping review. Methods: The present review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines. A comprehensive search was carried out across PubMed, Scopus, and Google Scholar databases to identify relevant studies published between January 2015 and January 2025. Eligible studies included randomized controlled trials (RCTs), case studies, and case series that reported yoga interventions for hypertension with blood pressure outcomes. 10 eligible studies were included and analyzed. Results: Eight RCTs, a case study, and a case series met the inclusion criteria. The different types of intervention studied were pranayama, asanas, Yoga Nidra, and integrative approaches combining yoga with naturopathy. Majority of studies reported statistically significant reduction in both systolic and diastolic blood pressure. Out of these interventions, sheetali pranayama and bhramari pranayama were most utilized. Notably, no significant adverse events were reported. Conclusion: Yoga may serve as an effective and safe adjuvant therapy for individuals with hypertension. However, the heterogeneity and poor standardization of methodologies and the lack of long-term follow-up suggest that further standardization and high-quality trials are required.